Petrology and origin of the Lar igneous complex of the Sistan suture zone, Iran - Boomeri, Mohammad; Moradi, Rahele; Bagheri, Sasan (Geologos, 2020)
The Oligocene Lar igneous complex is located in the Sistan suture zone of Iran, being emplaced in Paleocene to Eocene flysch-type rocks. This complex includes mainly intermediate K-rich volcanic (trachyte, latite and andesite) and plutonic (syenite and monzonite) rocks that belong to shoshonitic magma. The geochemical characteristics of the Lar igneous complex, such as an enrichment of LREE and LILE relative to HREE and HFSE, respectively, a negative anomaly of Ti, Ba and Nb and a positive anomaly of Rb and Th are similar to those of arc-type igneous rocks. Tectonic discrimination diagrams also show that rocks of the Lar igneous complex fall within the arc-related and post-collisional fields and K-enrichment of these rocks confirm the post-collisional setting. Based on geochemical features, the Lar igneous complex magma was derived from partial melting of a phlogopite-bearing, enriched and metasomatised lithospheric mantle source and the magma was affected by some evolutionary processes like fractional crystallisation and crustal contamination.